Exploring the Multidisciplinary Factors Affecting Sports Talent Identification - Xiang, Changqing; Tengku Kamalden, Tengku Fadilah; Liu, Hejian; Ismail, Normala (Frontiers in Psychology, 2022)
Talents are one of the most significant factors to promote the development of sports undertakings. The present study aimed to explore the factors affecting the identification of sport talents in China’s physical education curriculum. Based on the literature review, this paper puts forward a model to examine the influencing factors of sport talent identification in China’s physical education curriculum with structural equation modeling, and uses the structural equation modeling and factor analysis method to verify the hypothesis combined with the results of 310 effective questionnaires. The paper summarizes the influencing factors from four aspects and names them as physical, psychological, coaches and environmental. On the basis of relevant literature, the hypothesis model was established by structural equation modeling. The results show that the main factors affecting the identification of sport talents in physical education curriculum including personal physical quality performance, psychological quality, coach’s knowledge as well as the identification policies of schools to sport talents. The conclusion of this study can provide guidance for the reform of physical education curriculum, the growth of sport talents and the development of sport talents in China.